Ethical aspects of the interaction nurse-postpartum women with HIV/AIDS - Barroso, Léa Maria M.; Carvalho, Carolina Maria L.; Galvão, Marli T.G.; Vieira, Neiva F.C.; Barroso, Maria Graziela T. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: AIDS is a disease that brought along ethical dilemmas, due to its epidemic, clinic and social characteristics, requiring development onprofessional interaction applied in ethics. Objective: describing an interaction between nurse and postpartum women with HIV under ethical and pro-fessional perspective. Methods: describing, exploring and qualifying study developed in a public maternity in Fortaleza, Ceara, on November, 2004. The data collection was done by means of participating and daily observation in field. A schedule was used which allowed observing the criteria ofevaluation of the assistance provided to the postpartum women with HIV. Results: According to what was observed the nurse lets clear that the over-load of work makes it difficult to guarantee the quality of assistance. The absence of proper information and the non-fullfillment of respect to natural taboo and to privacy and intimacy of the patient were identified. Conclusion: it’s necessary to know the ethics code and make use of it in order tostraighten the ethical principles. The health care institutions need to adequate and demand the fullfillment of professional ethics.